The Greater Chaco Landscape : Ancestors, Scholarship, and Advocacy - Heitman, Carrie C.; Van Dyke, Ruth M. (Book collections on Project MUSE., 2021)
"Since mid-1970s, government agencies, scholars, tribes, and private industries have attempted to navigate conflicts involving energy development, Chacoan archaeological study, and preservation across the San Juan Basin. Examines both the imminent threat by energy extraction and ways of understanding Chaco Canyon--and Chaco-era great houses and associated communities"--